DOI: 10.33915/etd.2307
|View full text |Cite
|
Sign up to set email alerts
|

A detailed sequential extraction study of selenium in coal and coal-associated strata from a coal mine in West Virginia

Abstract: This study of the mode of occurrence and distribution of selenium in a rock core from southcentral West Virginia reveals that total selenium concentration varies by rock type. Rocks with total selenium >1 mg/kg were of circum-neutral pH based on acid base accounting data. No direct correlation was found between selenium concentration in the rocks and that of sulfur and/or total organic carbon. The distribution of total selenium was also controlled by stratigraphy. The amount of total selenium extracted from va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…6 Block coal bed through the Coalburg coal bed stratigraphic interval. Roy (2005) and Vesper and Roy (2006) did not find any strong correlation between Se and sulfur content or organic matter in rock samples.…”
Section: Comparison Of Se Concentration In Roof Parting Floor and mentioning
confidence: 86%
See 3 more Smart Citations
“…6 Block coal bed through the Coalburg coal bed stratigraphic interval. Roy (2005) and Vesper and Roy (2006) did not find any strong correlation between Se and sulfur content or organic matter in rock samples.…”
Section: Comparison Of Se Concentration In Roof Parting Floor and mentioning
confidence: 86%
“…Several recent studies have examined Se concentrations in various lithologies collected from cores drilled in coal-bearing strata in southern West Virginia (Jenkins and Schaer, 2005;Mullennex, 2005;Roy, 2005;Vesper and Roy, 2006). Samples in those studies were collected from different stratigraphic intervals, selected using different criteria, and categorized into different lithologic groups compared to this report.…”
Section: Discussion Selenium Concentration Lithology and Mineralogymentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the lengthy process associated with natural rock dissolution (Sparks, 1989), Roy (2005) and Pumure et al (2009) Se extracted from each sample (sandstone, claystone 1, claystone 2) ranged from 75-99%, 14-35%, and 9.0-14%, respectively. An additional study by Pumure et al (2010) found that 35% and 38% of total Se in shale samples from a southern WV surface mine were extractable by similar ultransonic methods.…”
Section: Desorption Of Seleniummentioning
confidence: 99%